1972
DOI: 10.1126/science.178.4063.867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colchicine, Colcemid, and Vinblastine on the Agglutination, by Concanavalin A, of Transformed Cells

Abstract: The sensitivity of transformed 3T3 fibroblasts to agglutination by concanavalin A is reduced by alkaloids that bind specifically to protein subunits of microtubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…We define A as the anchored state of the receptors (attached to the CBP) and F as the free state of the receptor (not attached to the CBP); these two states exist-in an equilibrium A =, F. Through this anchorage, the distribution of the receptors on the cell surface is affected by the state of the CBP. A similar suggestion has been made by Berlin and Ukena (16,17), who found that colchicine and vinblastine inhibited the agglutination of fibroblasts and polymorphonuclear leukocytes by Con A. (ii) Not only is It is important to consider how the cell surface receptors might be linked to this common network. Several findings may be pertinent.…”
Section: A Model For Receptor-cytoplasmic Interactionssupporting
confidence: 53%
“…We define A as the anchored state of the receptors (attached to the CBP) and F as the free state of the receptor (not attached to the CBP); these two states exist-in an equilibrium A =, F. Through this anchorage, the distribution of the receptors on the cell surface is affected by the state of the CBP. A similar suggestion has been made by Berlin and Ukena (16,17), who found that colchicine and vinblastine inhibited the agglutination of fibroblasts and polymorphonuclear leukocytes by Con A. (ii) Not only is It is important to consider how the cell surface receptors might be linked to this common network. Several findings may be pertinent.…”
Section: A Model For Receptor-cytoplasmic Interactionssupporting
confidence: 53%
“…CBP appear to be essential for the selective removal of lectin receptors from the plasma membrane. This seems difficult to reconcile with the concept that CBP anchor surface elements geographically, a possibility originally suggested by us (6)(7)(8) and recently elaborated by Edelman (25). This paradox is resolved if we postulate that CBP, rather than anchoring surface elements, are required for their directed movement.…”
Section: Discussionmentioning
confidence: 89%
“…It thus seems probable that the effects of colchicine are a result of its inhibition of tcrotubule Moreover, the effects of preincubation with colchicine do not persist after the cells are broken, nor does colchicine affect directly either basal or hormone-stimulated adenylate cyclase activity in leukocyte membrane preparations (data not shown), even though these preparations respond readily to the hormones themselves, suggesting that the colchicine effect on cyclic AMP levels is a result of its interaction with cytoplasmic, rather than membrane-associated, tubulin. It has been suggested that colchicine-sensitive cytoplasmic structures (presumably microtubules) may interact with the cell membrane in such a way as to place constraints on the mobility of certain receptors (22)(23)(24)(25). Previous work has involved primarily lectin-binding receptors.…”
Section: Discussionmentioning
confidence: 99%